2018
DOI: 10.14210/at.v3n2.p01-35
|View full text |Cite
|
Sign up to set email alerts
|

ETNOGRAFIA E TURISMO: Um Estudo das Percepções e Sentimentos de Crianças Residentes na Ilha Do Mel – PR

Abstract: A etnografia é uma metodologia associada às investigações antropológicas, utilizada como estratégia de registro de informações coletadas no trabalho de campo. A etnografia vem sendo descoberta como uma abordagem teórica que amplia a compreensão da dinâmica da atividade nos estudos do turismo. Para os estudos com crianças e suas infâncias a abordagem etnográfica implica na aceitação, por parte das crianças em participar do estudo e do pesquisador em compreender as singularidades do universo infantil. Nesse sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Despite this role has already been socially played, some lodging facilities insist in keep minimal planning for this public, limiting themselves only to adults' needs. Regarding the relationship Childhood and Tourism, Piola, Andrade and Kushano (2018) quoted by Kushano (2010) pointed that "it was observed that the touristic activity is a mean of leisure, and it contributes to one's learning process and development. Specially children, who may learn the others' culture by experiencing the new, as well as what is familiar".…”
Section: Child Consume and Tourismmentioning
confidence: 99%
“…Despite this role has already been socially played, some lodging facilities insist in keep minimal planning for this public, limiting themselves only to adults' needs. Regarding the relationship Childhood and Tourism, Piola, Andrade and Kushano (2018) quoted by Kushano (2010) pointed that "it was observed that the touristic activity is a mean of leisure, and it contributes to one's learning process and development. Specially children, who may learn the others' culture by experiencing the new, as well as what is familiar".…”
Section: Child Consume and Tourismmentioning
confidence: 99%